PENGARUH SUKU BUNGA, PROSEDUR PELAYANAN DAN KECEPATAN PELAYANAN TERHADAP KEPERCAYAAN NASABAH DAN KEPUTUSAN PENGAMBILAN KREDIT PADA BRI DI WILAYAH SURAKARTA - Santosa, Jarot; Mahendra, Denny (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2019)
The purpose of this study is to find out and test the influence of interest rates, service procedures and the speed of service on customer trust and decision to take credit at BRI in the Surakarta Region. The population in this study is credit customers above Rp. 500,000,000.00 at BRI in the Surakarta Region with 880 customers. The sample in this study is 10% of the population that is equal to 88 customers, rounded up to 100 respondents in order to get better results. The analysis technique in this study uses the instrument test, t test, F test, test coefficient of determination and path analysis. The Hypothesis Test results are that interest rates have a significant effect on customer trust. Service procedures have a significant effect on customer trust. Service speed has no significant effect on customer trust. Interest rates have a significant effect on credit decision making. Service procedures have a significant effect on credit decision making. Service speed has a significant effect on credit decision making. Trust has a significant effect on credit decision making. The results of the F test can be summed up together with variable interest rates, service procedures, service speed, and trust influencing credit decision making. The results of the coefficient of determination show that 98.2% interest rates, service procedures and service speed influence the decision to take credit at BRI in the Surakarta region. The results of path analysis show that the direct effect of service speed on credit decision making is the most dominant influence in influencing credit decision making at BRI in the Surakarta region.